2018
DOI: 10.1002/ijc.31526
|View full text |Cite
|
Sign up to set email alerts
|

Single CpG hypermethylation, allele methylation errors, and decreased expression of multiple tumor suppressor genes in normal body cells of mutation‐negative early‐onset and high‐risk breast cancer patients

Abstract: To evaluate the role of constitutive epigenetic changes in normal body cells of BRCA1/BRCA2‐mutation negative patients, we have developed a deep bisulfite sequencing assay targeting the promoter regions of 8 tumor suppressor (TS) genes (BRCA1, BRCA2, RAD51C, ATM, PTEN, TP53, MLH1, RB1) and the estrogene receptor gene (ESR1), which plays a role in tumor progression. We analyzed blood samples of two breast cancer (BC) cohorts with early onset (EO) and high risk (HR) for a heterozygous mutation, respectively, alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 44 publications
(50 reference statements)
1
21
0
Order By: Relevance
“…Alleles with > 50% aberrantly (de)methylated CpGs in DBS are considered as functionally relevant epimutations. Consistent with an epimutation screen in breast cancer susceptibility genes [3], we considered EMRs > 1% as elevated and EMRs > 2.5% as likely pathogenic constitutive epimutations. Using the above-described classi cation, we did not detect any APC epimutations in broblasts of patient 1N08.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alleles with > 50% aberrantly (de)methylated CpGs in DBS are considered as functionally relevant epimutations. Consistent with an epimutation screen in breast cancer susceptibility genes [3], we considered EMRs > 1% as elevated and EMRs > 2.5% as likely pathogenic constitutive epimutations. Using the above-described classi cation, we did not detect any APC epimutations in broblasts of patient 1N08.…”
Section: Resultsmentioning
confidence: 99%
“…Next-generation sequencing (NGS) libraries for DBS were generated as described previously [3]. PCR ampli cation of APC, CDKN2A, TP53, and RAD9A was performed using primers containing a target-speci c part and partial adapter overhangs (supplementary Table 2).…”
Section: Deep Bisul Te Sequencing (Dbs)mentioning
confidence: 99%
See 1 more Smart Citation
“…One of these communities is that of physicians involved in the diagnosis of genetic diseases and using the Gen-searchNGS tool [28]. This Java software analyzes next-generation sequencing data (NGS) to detect changes in DNA sequences for the diagnosis of genetic diseases [29,30]. In order to be able to easily integrate into any Java software, including Gen-searchNGS, TFC capabilities the POP-Java tool [31,32] was used.…”
Section: Trusted Friend Computingmentioning
confidence: 99%
“…Methylation of peripheral blood-derived DNA is related to the occurrence of tumors, and individual differences in methylation can re ect an individual's susceptibility to tumors [17,18]. In addition, it is reported that the effect of environmental factors on methylation status also found in peripheral blood and environmental factors contribute to CRC risk.…”
Section: Introductionmentioning
confidence: 99%